Metal-dielectric structures for high resolution imaging - Wang, Y. K. (2013)
Since Pendry’s theoretical proposition of the perfect lens, extensive researches have been carried out in the field by a number of groups and various lenses and structures have been reported. In this article, we present and discuss light transmission in a vertical multilayered metal-dielectric structure and a metal chain array consisting of silver spheres with different diameters. For the incident wavelength of 660 nm, light can transmit a longer distance in the vertical multilayer structure due to low transmission loss. For the metal nanoparticle chain structure with an incident wavelength of 508 nm, the output light intensity can be greatly enhanced by adding a small sphere to the input end and output end, respectively as it is believed to enhance the coupling of the field into the structure and decoupling of the field from the structure, respectively.